The protective properties of resveratrol against glycerol-induced acute kidney injury in rats - Mohammadreza Baghishani; Soghra Mehri; Tahereh Aminifard; Amirhossein Jafarian; Hossein Hosseinzadeh (Avicenna Journal of Phytomedicine)
Objective: After rhabdomyolysis, muscle tissue releases substances such as myoglobin, creatine kinase, and electrolytes into the bloodstream, potentially leading to acute kidney injury (AKI). Resveratrol (RSV) is a polyphenol compound with anti-inflammatory and antioxidant effects and it is found in various plants. This research evaluated the protective effects of RSV in rhabdomyolysis-induced AKI in rat kidneys.Materials and Methods: Thirty-six male Wistar rats were randomly assigned to six groups (n=6): 1) control (normal saline), 2) glycerol only (10 ml/kg, intramuscular), 3, 4, and 5) glycerol +RSV (5, 10, and 25 mg/kg, intraperitoneal injection) and 6) RSV (25 mg/kg). After 4 days, pathological alterations and the level of blood urea nitrogen (BUN) and serum creatinine were determined. Malondialdehyde (MDA), glutathione (GSH), neutrophil gelatinase-associated lipocalin (NGAL), and tumor necrosis factor-α (TNF-α) proteins were investigated in rat kidneys. Results: Injection of 50% glycerol (10 ml/kg, IM) resulted in pathological lesions, elevated levels of MDA (p<0.001), BUN (p<0.01), serum creatinine (p<0.001), TNF-α (p<0.01), and NGAL protein (p<0.001), and decreased GSH content (p<0.001) compared to the control animals. These findings indicated AKI induced by rhabdomyolysis. RSV (25 mg/kg) administration significantly decreased serum creatinine, BUN, MDA, NGAL, and TNF-α levels compared to the glycerol group. Histopathologically, tubule necrosis, myoglobin cast formation and glomerular atrophy increased in the glycerol group and reduced in animals that received RSV.Conclusion: In the glycerol-induced AKI rat model, RSV administration alleviated renal dysfunction by reducing oxidative stress and inflammatory responses.